Women, Inclusiveness and Participatory Governance in Nigeria's Niger Delta: A Focus on Shell's Model of Community Development in the Region. (1st December 2016) - Isike, Christopher
Abstract: This paper analyzed the influence of adaptive collaborative governance on women's inclusion and participation in governance in the Niger Delta of Nigeria with focus on Shell Petroleum Development Company (SPDC's) community development model; the Global Memorandum of Understanding (GMoU). It used the inclusiveness, governance and transparency scores in Shell's internal evaluation (SCOTDI) of 19 active GMoU clusters in the Niger Delta as indices to measure the performances of 10 selected clusters viz-a-viz their inclusion of women in their governance structures and processes. The 10 supervisory NGOs of these clusters were also interviewed in a Focus Group Discussion (FGD). The data generated from the SCOTDI evaluation and FGD was qualitatively analyzed in line with the objectives of the paper and the findings presented and discussed accordingly. A key finding showed governance improved with women's inclusion in decision-making. Although challenges around the quality of women's representation persist, the paper concludes that the GMoU has potential for mediating the governance and development challenges the Niger Delta faces.